ARGUMENTASIÂ ISLAMÂ DALAMÂ POLEMIKÂ UNDANGâ€ UNDANGÂ KESETARAANÂ GENDERÂ DIÂ INDONESIA - Marhumah, Ema (Sunan Kalijaga State Islamic University & The Asia Foundation, 2012)
In the substantive understanding of religion, there is no differentiation between man and woman. The Al-Quran enshrines the principles of justice, equality, democracy and muasyarahbilmaâ€™ruf(humanizing actions). This manner of interpretation must become the basis in understanding the connection between religious teachings and the Draft Law on Gender Equality. To see Islam in a theological light, indeed there are several religious texts which directly differentiate man and woman, but what we must realize is that the Quran which was bestowed upon the Prophet not only contained provisions on how to life oneâ€™s life, but also the method to organize life itself. Understanding Islam depends greatly on our manner of interpretation. If a patriarchal reading of Islam were to be fostered, then the result will be rejection of the draft law on the pretenses of religious desecration. However, if we were to understand religion on the basis of equality, then a solution to the existing problem will surely be found.